Plant traits as potential drivers of timber value in the Dipterocarpaceae - Malik, Nazrin; Edwards, David; Freckleton, Robert P. (John Wiley and Sons, 2026)
Southeast Asian tropical forests are vital sources of high-value timber and non-timber forest products (NTFPs). This study investigates the relationship between plant traits, wood density, and timber market value within the Dipterocarpaceae family, a critical contributor to the global tropical timber trade and a key structural component of many forests in Southeast Asia. Using a phylogenetic approach, we explored the correlation of morphological and life-history traits with timber price. Our results show that wood density is significantly associated with higher timber prices, and this relationship is strongly influenced by phylogenetic dependence. We found no evidence linking timber value to the conservation status of dipterocarp species, suggesting that economic exploitation does not necessarily correlate with species endangerment. These findings emphasize the importance of understanding the evolutionary patterns driving economically valuable traits in timber species, which can guide sustainable forest management and conservation strategies in Southeast Asia.